2007
DOI: 10.1215/15228517-2007-008
|View full text |Cite
|
Sign up to set email alerts
|

Case study of intracerebral plasmacytoma as an initial presentation of multiple myeloma

Abstract: Cerebral involvement is an uncommon complication of multiple myeloma. We report on a 64-year-old man hospitalized for a partial seizure. MRI showed two intracerebral lesions, which proved to be plasmacytomas. After complete staging, we retained the diagnosis of immunoglobulin G lambda-type multiple myeloma with CNS involvement. Cytogenetic analysis of plasma cells detected a deletion in the p53 gene at 17p13.1. Despite cranial radiotherapy and systemic chemotherapy, the patient's disease progressed rapidly and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 5 publications
(5 reference statements)
0
27
0
Order By: Relevance
“…When involving the skull base as in our observation, plasma cells neoplasms could be asymptomatic. If it's a voluminous mass it may result in tumefaction, pain, headache, single or multiple cranial nerve palsies, or seizure if intracranial extension [6,7]. In our case the patient had a diplopia caused by the left sixth nerve palsy by compression and temporal headache.…”
Section: Discussionmentioning
confidence: 61%
“…When involving the skull base as in our observation, plasma cells neoplasms could be asymptomatic. If it's a voluminous mass it may result in tumefaction, pain, headache, single or multiple cranial nerve palsies, or seizure if intracranial extension [6,7]. In our case the patient had a diplopia caused by the left sixth nerve palsy by compression and temporal headache.…”
Section: Discussionmentioning
confidence: 61%
“…Only individual case reports and small series described such symptomatology, including cranial nerve palsy [8], visual loss [6] or motor seizures [13]. The apoplectic symptoms are even more uncommon in MM.…”
Section: Discussionmentioning
confidence: 99%
“…As multiple myeloma involvement of the CNS is rare [13], intracranial haemorrhage of the tumour is an extraordinary event in clinical practice. Only one case report of a 57-year-old male can be found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…These extramedullary plasma cell neoplasms are most commonly seen in the respiratory tract followed by gastrointestinal tract, central nervous system, bladder, breast, testis and lymph nodes [2,3,4]. Central nervous system plasmacytomas are very rare; as per our literature review less than 20 cases have been reported in the English literature [5][6][7][8][9][10][11]. Here we present our experience with a dural plasmacytoma as the initial sign of disease recurrence in a patient with systemic multiple myeloma.…”
Section: Introductionmentioning
confidence: 87%